2017
DOI: 10.1007/s00018-017-2537-6
|View full text |Cite|
|
Sign up to set email alerts
|

Stress and the nonsense-mediated RNA decay pathway

Abstract: Cells respond to internal and external cellular stressors by activating stress response pathways that re-establish homeostasis. If homeostasis is not achieved in a timely manner, stress pathways trigger programmed cell death (apoptosis) to preserve organism integrity. A highly-conserved stress pathway is the unfolded protein response (UPR), which senses excessive amounts of unfolded proteins in the ER. While a physiologically beneficial pathway, the UPR requires tight regulation to provide a beneficial outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 170 publications
(374 reference statements)
2
86
0
Order By: Relevance
“…A broad bioinformatic analysis on the RNASeq data from human cell lines with knockdowns of key NMD components UPF1, SMG6 or SMG7 demonstrated that the endoneucleolytic (SMG6-mediated) and exonucleolytic (SMG 5/7 mediated) decay routes are redundant, degrading mRNAs with introns in 3 UTR regions [43]. It has been observed that NMD targets with 5 upstream open reading frames (uORFs) and long 3 UTRs tend to be categorized as transcription factors, stress response genes and oncogenes [31,68].…”
Section: Nmd As a Regulator Of The Immune Response And Viral Replicationmentioning
confidence: 99%
“…A broad bioinformatic analysis on the RNASeq data from human cell lines with knockdowns of key NMD components UPF1, SMG6 or SMG7 demonstrated that the endoneucleolytic (SMG6-mediated) and exonucleolytic (SMG 5/7 mediated) decay routes are redundant, degrading mRNAs with introns in 3 UTR regions [43]. It has been observed that NMD targets with 5 upstream open reading frames (uORFs) and long 3 UTRs tend to be categorized as transcription factors, stress response genes and oncogenes [31,68].…”
Section: Nmd As a Regulator Of The Immune Response And Viral Replicationmentioning
confidence: 99%
“…4). In general, oxidative stress suppresses NMD in order to enhance the ability of cells to survive ROS toxicity (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…S5B). To better understand how these pathways were regulated by galactose culture, we examined members of Nonsense-mediated mRNA decay (NMD) enhanced by the Exon Junction Complex (EJC), a surveillance pathway that eliminates mRNAs containing premature translation stop codons (26). Visualization of these proteins on a heatmap revealed that their basal expression was low in mAKT-expressing cells cultured in glucose and that short-term galactose induced higher expression ( Fig.…”
Section: Proteomic Analysis Reveals Enriched Nonsense-mediated Mrna Dmentioning
confidence: 99%
“…One possibility is that it is part of a feedback network to control muscle mass. Various stressors are known to inhibit NMD, probably as a means to regulate biological responses [26]. If exercise stress also inhibits NMD, this would be predicted to amplify myogenesis as a means to build muscle mass.…”
Section: Perspectivementioning
confidence: 99%
“…One line of evidence for this is the finding that mutations in the yeast UPF1 RING domain disrupt NMD [23]. Another line of evidence is studies demonstrating UPF1-dependent decay of peptides translated from PTC-containing transcripts [26][27]. In the future, it will be intriguing to determine whether the mechanism responsible for this UPF1 dependent peptide decay in yeast is UPF1’s E3 ligase activity.…”
Section: Perspectivementioning
confidence: 99%